Pediatric Nurses' Perceptions of Medication Safety and Medication Error: A Mixed Methods Study. Issue 2 (3rd April 2018) - Alomari, Albara; Wilson, Val; Solman, Annette; Bajorek, Beata; Tinsley, Patricia
ABSTRACT: This study aims to outline the current workplace culture of medication practice in a pediatric medical ward. The objective is to explore the perceptions of nurses in a pediatric clinical setting as to why medication administration errors occur. As nurses have a central role in the medication process, it is essential to explore nurses' perceptions of the factors influencing the medication process. Without this understanding, it is difficult to develop effective prevention strategies aimed at reducing medication administration errors. Previous studies were limited to exploring a single and specific aspect of medication safety. The methods used in these studies were limited to survey designs which may lead to incomplete or inadequate information being provided. This study is phase 1 on an action research project. Data collection included a direct observation of nurses during medication preparation and administration, audit based on the medication policy, and guidelines and focus groups with nursing staff. A thematic analysis was undertaken by each author independently to analyze the observation notes and focus group transcripts. Simple descriptive statistics were used to analyze the audit data. The study was conducted in a specialized pediatric medical ward. Four key themes were identified from the combined quantitative and qualitative data: (1) understanding medication errors, (2) the busy-ness of nurses, (3) the physical environment, and (4) compliance with medication policy and practice guidelines. Workload, frequent interruptions to process, poor physical environment design, lack of preparation space, and impractical medication policies are identified as barriers to safe medication practice. Overcoming these barriers requires organizations to review medication process policies and engage nurses more in medication safety research and in designing clinical guidelines for their own practice.